KARYA TULIS ILMIAH BAGI GURU MADRASAH: PELATIHAN DAN PUBLIKASI - Latifah, Eny; Yusuf, Yusuf (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Encouraging professional teachers in the field of writing and creating works of scientific intellect to improve quality with training and publication of scientific papers is very important to do. This PKM aims to provide training in making scientific articles and reference books for Madrasah Ibtidaiyah Mazroatul Ulum 02 Paciran and MI 02 Muhammadiyah Cendoro Tuban teachers. The method applied is training and assistance in publishing scientific papers. The results of PKM are training in making articles to be published in national journals given at MI 02 Muhammadiyah Cendoro tuban and making textbooks given at MI 02 Mazroatul Ulum Paciran. The scientific work that can be realized is a scientific article entitled Mathematical Connection Ability Based on Reflective and Implusive Cognitive Styles (Case Study on Class Viii A Students of Smp Negeri 1 Palang Tuban) published in the PHENOMENON journal: Multidisciplinary Journal of Sciences and Research. While the work of the teacher's masterpiece reference book MI 02 Mazroatul Ulum Paciran with the title Madrasah Science Competition was published in YSIM Banten.